The Indications of The Environmental in Wadi Al Ajradi in the Imam Turki bin Abdullah Reserve During Holocene Period - Alanazi, Maha Awwad (Journal of Humanities & Social Sciences, 2024)
Wadi Al Ajardi is located along the southeast of Imam Turki Bin Abdullah Royal Natural Reserve (Al-Taisiya), north of Al-Qassim Province. It is one of the ancient hydrological networks, which formed during the rainy periods of the Late Quaternary. Together with Wadi Al-Rummah and Wadi Al-Batin in the east, it represents a part of a great river that dominated these areas of Saudi Arabia.The researchers pay attention to studying the environmental changes of Wadi Al Ajardi basin for the sake of rebuilding the ancient environment of Imam Turki Bin Abdullah Royal Natural Reserve. This research aims to clarify the environmental changes experienced by this area of Imam Turki Bin Abdullah Royal Natural Reserve and recognize the relationship between the ancient stream of Wadi Al Ajardi and the stream of Wadi Al-Rummah, particularly in the Holocene Epoch. Moreover, it demonstrates the most prominent features of the environmental and climatic changes that coincide with the development of Wadi Al Ajardi.The research used laboratory techniques and analyses, including Radiocarbon Dating (14C), X-Ray Diffraction (XRD), and Grain size analysis, in addition to extensive fieldwork. The research findings contributed to depicting the past of Imam Turki Bin Abdullah Royal Natural Reserve in this region of Saudi Arabia, where Wadi Al Ajardi witnessed great activity in the early Holocene (approximately 9544 - 9695 BPCal) and reconstructing the ancient river network that dominated during the rainy ages.
Keywords: Holocene; X-Ray Diffraction (XRD); Imam Turki Bin Abdullah Royal Natural Reserve (Al-Taisiya); Radiocarbon Dating (14C)